High Thermal Equivalence Solid Thermal Energy Storage Utilizing Mixed Halide Salts Combined with Nanoporous Cores - Enas Eltnay; Luttfia Hadod (AlQalam Journal of Medical and Applied Sciences, 2025)
The shift to renewable energy generation has also enhanced the need to have an extensive and efficient thermal energy storage (TES) technology that can overcome the supply-demand variations. The paper performs research into the improvement of TES performance by incorporating high-tech nanomaterials into mixed halide and solid-state composite systems. Special emphasis is made on the addition of high-conductivity materials like porous carbon structures, two-dimensional copper substances, and bimetallic nanoparticles to enhance the thermal conductivity, phase stability, and cycle life. It is found that through experimentation, thermal conductivity (as high as 35-42%) improved, latent heat retention (more than 90 percent after 150 cycles), and phase segregation were greatly decreased relative to standard halide storage materials. Leakage and structural degradation are also avoided by using nano-encapsulation strategies when charging and discharging are done repeatedly. The findings illustrate that nanostructuring and composite engineering have considerable synergy to provide high-equivalence solid TES media, which can be applied to more secure and longer-lasting energy control solutions in solar power and grid-scale storage systems. Altogether, this work contributes to the idea of sustainable use of thermal energy based on the material and offers the basis of optimisation and massive implementation of the next generation of thermal energy storage technologies.